Genetic Transformation in Citrus. (25th July 2013) - Donmez, Dicle; Simsek, Ozhan; Izgu, Tolga; Aka Kacar, Yildiz; Yalcin Mendi, Yesim
Abstract : Citrus is one of the world's important fruit crops. Recently, citrus molecular genetics and biotechnology work have been accelerated in the world. Genetic transformation, a biotechnological tool, allows the release of improved cultivars with desirable characteristics in a shorter period of time and therefore may be useful in citrus breeding programs. Citrus transformation has now been achieved in a number of laboratories by various methods. Agrobacterium tumefaciens is used mainly in citrus transformation studies. Particle bombardment, electroporation, A. rhizogenes, and a new method called RNA interference are used in citrus transformation studies in addition to A. tumefaciens . In this review, we illustrate how different gene transformation methods can be employed in different citrus species.